Indonesian pre-war Chinese Peranakan writings as Indonesian ‘post-colonial’ literary texts. - Sim , Chee Cheang (Universiti Kebangsaan Malaysia, 2008)
Gayatri Spivak's dispute about the abilities of the silenced subaltern in colonial hegemonies has contributed to a possible paradigm shift in the focus of postcolonial critical analysis from literature published after colonialism to an awareness of literature by the natives during and before colonialism albeit in another language, This article aim toprove that a 'post' colonial phenomenon begins at the moment of encounter between the colonial and subject as evidenced in the pre-war Chinese Indonesian writings from 1897-1942. The content and intent of some 3,000 over copies raised pertinent evidence to the existence of 'post' colonial texts appearing at the dawn of national consciousness rather than post-independence as suggested by Homi K. Bhabha when discoursing a period of mimicry in postcolonial literature. An analysis of pre-war Tionghoa pemnakan fiction novels will uncover elements of 'post' colonial discourse, which includes a period of 'in-authenticity', a search for freedom, a national hybrid identity and an anti-colonial stand in a language of their own during Dutch colonialism in the East Indies.